Impact of Recent Studies for the Treatment of Intracerebral Hemorrhage - Sembill, Jochen; Huttner, Hagen; Kuramatsu, Joji (Current Neurology and Neuroscience Reports, 2018)
PURPOSE OF REVIEW: The present review will cover most recent and important studies on acute treatment of intracerebral hemorrhage (ICH). RECENT FINDINGS: Overly pessimistic prognostication in ICH may deny meaningful recovery achieved by specialized neurocritical care. Hematoma enlargement represents the most important target of acute ICH care, which is reduced by aggressive blood pressure management (targeting a systolic blood pressure of 140 mmHg) and appropriate hemostatic treatment especially in anticoagulation-associated ICH (INR reversal using prothrombin complex concentrates, eventually idarucizumab, andexanet, or tranexamic acid). Surgical treatment strategies involving fibrinolytics either used for direct hematoma lysis or used for intraventricular clot removal with/without additional lumbar drainage show great promise. Further novel treatment strategies are underway and need validation or evaluation strongly warranting well-designed future ICH research. Several randomized and large-sized observational studies have considerably expanded the field and the evidence on how to treat acute ICH patients. Yet, the one breakthrough intervention to improve functional outcome is still missing, though various treatment concepts possibly interacting with one another have been evaluated and such treatment bundle may improve patients' outcome.
EVALuna2:201936